Development of Rutile Titanium Oxide Thin Films as Battery Material Component Using Atomic Layer Deposition. Issue 13 (23rd August 2019) - Kia, Alireza M.; Bönhardt, Sascha; Zybell, Sabine; Kühnel, Kati; Haufe, Nora; Weinreich, Wenke
Abstract : Herein, growth kinetics, crystal structure, and the uniformity of titanium oxide (TiO2 ) thin films prepared using atomic layer deposition (ALD) and plasma‐enhanced ALD (PE‐ALD) are studied. TiO2 thin films are grown using titanium tetrachloride (TiCl4 ), water, and oxygen precursors. Using ALD, TiO2 is grown in the temperature range of 270–310 °C thermally and in the range of 300–400 °C with PE‐ALD. In spite of the plasma process yielding better uniformity on planar structures, the optimized thermal process provides a remarkable conformal step coverage within deep trenches. In addition, the change in the crystal structure and phase transitions of TiO2 is presented herein. This is attempted at using TiO2 as a component material to grow lithium titanate (LTO) as an electrode material in solid‐state lithium‐ion batteries (LIBs). Thereby, different substrates are used. In comparison to the silicon (Si) substrate, silicon oxide (SiO2 ) and titanium nitride (TiN) lead to crystal phase transformation while annealing. Measurements are performed using in situ high‐temperature X‐ray diffraction (HT‐XRD). It is also shown that when TiN is sandwiched between TiO2 and the silicon substrate, the TiO2 thin film (25 nm) gradually changes from an anatase to a rutile structure. Abstract : Herein, the development of rutile titanium oxide (TiO2 ) thin‐film deposition using atomic layer deposition (ALD) is presented. Changes in the crystal structure and phase transitions of TiO2 are shown with the help of in situ high‐temperature X‐ray diffraction (HT‐XRD). Using silicon oxide (SiO2 ) or titanium nitride (TiN) between TiO2 and the Si substrate leads to crystal phase transformation while annealing.